Analisis Efektivitas Penerapan Maintenance pada Mesin Produksi Furniture (Rustic) Studi Kasus di PT. Rajawali Perkasa Furniture - Ratri Rahmawati; Sigit Arrohman; Rianto Wibowo; Bella Chintya Reira Christata; Heni Risnawati; Tuti Nadhifah (Jurnal INOVATOR, 2026)
Rustic wood refers to a type of wood that has a rough, natural appearance, and often retains the original characteristics of the wood. The term "rustic" describes a style or appearance that is simple, old-fashioned, and rustic in nature. Rustic wood is often used in interior and exterior design to create a warm, natural atmosphere. The research methodology was carried out by searching for literature studies collected from journals, papers and the internet. Conduct interviews with supervisors and PT employees. Rajawali Perkasa Furniture in the field. As well as direct observations in the field to find solutions related to problems that occur to take corrective solutions in accordance with company procedures. The maintenance carried out to repair Rustic machines is Preventive Maintenance. A maintenance system that is carried out regularly to ensure the condition of the machine and extend the life of the machine. Preventive maintenance is carried out regularly to prevent damage to the equipment so that if minor damage is found it can be repaired immediately. With planned maintenance, PT Rajawali Perkasa Furniture aims to find symptoms of damage to equipment before it experiences fatal damage, keep its production equipment machines in optimal condition, reduce the risk of damage, and increase overall productivity.